Biosynthesis uses, and defensive mechanisms of kauralexins and zealexins against fungi that attack maize (Zea mays) crops- An Review: Biosynthesis uses, and defensive mechanisms of kauralexins and zealexins against fungi that attack maize (Zea mays) crops - K. Karthik,; R. Priyanka,; Nithiyanantham, S.; C. Ragavendran, (Vietnam Journal of Science and Technology, 2025)
Fungal pathogens have a high effect on maize crops, where it leads to heavy loss of yield production globally. Secondary metabolites are biochemical compounds that play a crucial role in the stress and defense mechanism of plants. It controls several biotic and abiotic stresses and their related side effects. The fungi cause high-impact diseases to bio-organisms such as plants, animals, and humans. Evidently, throughout the world, a notable feed and used industrial product source is "Corn". Earlier studies have shown diverse approaches in plant defense mechanisms for plant growth and development. Here, we can see short-overview about the phytoalexin derivatives namely labdane-type diterpenoids kauralexins and acidic sesquiterpenoids zealexins biosynthesis, mode of action against fungal pathogens in maize crops. Additionally, past and current trend approach on plant-pathogen interactions used bioinformatics and metabolomic tools approach for disease resistance, database tools of plant metabolomics, and especially focused on resources database tools of plant-fungus interactions. Furthermore, this review is to pointout the “Phytoalexins” derivative bioactive diterpenoid compounds of kauralexins & zealexins antifungal defense mechanisms in maize (Z.mays) crops.